PROGRAM EDUKASI BERBASIS KELUARGA DALAM MENINGKATKAN DUKUNGAN KELUARGA PADA LANSIA DENGAN HIPERTENSI - Mananggel, Sjatrida L.; Lamonge, Annastasia Sintia; Polii, Grace B. (Lasalle Health Journal, 2023)
Introduction: Hypertension is a disease that needs to be controlled because it can become chronic. Family-based education programs are designed as an alternative to increase knowledge, compliance and even support for patients and their families. Objective: to determine the effectiveness of family-based education programs in increasing family support for elderly people with hypertension. Method: True experimental design: pretest – posttest design (before – after design). The population is elderly people with hypertension who live with their families. The sample size was 32 participants consisting of 16 experimental and 16 controls. The sampling technique is simple random sampling. Results: Wilcoxon test results: difference in average family support before and after education in both the experimental group (p value 0.001) and the control level of maturity (p value 0.587) which means there is an increase in knowledge in the experimental group. Test of differences using Mann-Whitney between the experimental and control groups with pretest results (p value 0.059) and posttest (p value 0.000), meaning that there are differences in family support between the experimental group and the control group. The experimental group experienced increased family support. Conclusion: This educational program is effective in increasing family support for elderly people with hypertension. So that it can be used by community health center nurses and cadres to educate patients and families in efforts to control hypertension in the community.